The Asian clam Corbicula fluminea in Ecuador: dispersion and diversity of occupied environments - Lodeiros, C. (2025)
Populations of invasive species can have a negative impact on the natural environment and socioeconomic effects of artificial systems. The relationship of Corbicula fluminea with humans, together with the its great adaptive-reproductive capacity, make it one of the most expansive species of invasive bivalves worldwide. Here we report on the dispersion of C. fluminea, and based on genetic analysis we describe the presence and potentially negative effect of this species for the first time in an anthropic environment, an aquaculture facility in Ecuador.